Reappraisal of Campanula rotundifolia var. bulgarica Nejceff—a neglected taxon from Central Stara Planina Mountain, Bulgaria - Marinov, Yulian; Stoyanov, Stoyan (Phytotaxa, 2017)
Campanula rotundifolia var. bulgarica Nejceff, a neglected taxon in the Bulgarian flora with currently uncertain status, was collected and studied at its locus classicus in the Sokolna (Koru Dere) Reserve of Central Stara Planina Mountain. A detailed morphological analysis of Nejceff’s original material and other related species clearly indicates that this is a distinct taxonomic entity worthy of species rank. Campanula nejceffii, stat. nov. is distinguished by a combination of its pubescent habit, ovoid to elliptic-lanceolate cauline leaves, clearly spreading to reflexed narrowly triangular-lanceolate calyx teeth, erect buds and flowers. Complete species description and comparison with selected species in the C. rotundifolia group are given. The lectotypes of two taxa—C. rotundifolia var. bulgarica Nejceff and C. rotundifolia subsp. neicevii f. pirinica Stoj. & Acht. are designated by the authors.